The Role of Motivation, Compensation, and Career Development on Employee Performance Through Job Satisfaction in the Digital Era - Ristriyani Ristriyani; Efriyani Sumastuti; Qristin Violinda (Institute Of Advanced Knowledge and Science, 2026)
This study aims to analyze the influence of motivation, compensation, and career development on employee performance through job satisfaction as a mediating variable in the context of human resource transformation in the digital era. The research was conducted at the Department of Communication, Informatics, Statistics, and Encryption of Semarang City using a quantitative approach and census method involving 143 employees, both civil servants and non-Civil servants. Data analysis was performed using Partial Least Squares (PLS) with the SmartPLS software. The results show that motivation, compensation, and career development have a significant effect on both job satisfaction and employee performance. Furthermore, job satisfaction effectively mediates the relationship between those variables and employee performance. These findings emphasize the importance of both internal and external factors in improving public sector employee performance, especially in facing the challenges of digital bureaucracy. This research provides empirical and practical contributions to human resource management in local government institutions.